Heat Shock-Induced Dephosphorylation of Eukaryotic Elongation Factor 1BδL by Protein Phosphatase 1 - Kaitsuka, Taku; Tomizawa, Kazuhito; Matsushita, Masayuki (Frontiers in Molecular Biosciences, 2021)
Several variant proteins are produced from EEF1D, including two representative proteins produced via alternative splicing machinery. One protein is the canonical translation eukaryotic elongation factor eEF1Bdelta1, and the other is the heat shock-responsive transcription factor eEF1BdeltaL. eEF1Bdelta1 is phosphorylated by cyclin-dependent kinase 1 (CDK1), but the machinery controlling eEF1BdeltaL phosphorylation and dephosphorylation has not been clarified. In this study, we found that both proteins were dephosphorylated under heat shock and proteotoxic stress, and this dephosphorylation was inhibited by okadaic acid. Using proteins with mutations at putative phosphorylated residues, we revealed that eEF1Bdelta1 and eEF1BdeltaL are phosphorylated at S133 and S499, respectively, and these residues are both CDK1 phosphorylation sites. The eEF1BdeltaL S499A mutant more strongly activated HSPA6 promoter-driven reporter than the wild-type protein and S499D mutant. Furthermore, protein phosphatase 1 (PP1) was co-immunoprecipitated with eEF1Bdelta1 and eEF1BdeltaL, and PP1 dephosphorylated both proteins in vitro. Thus, this study clarified the role of phosphorylation/dephosphorylation in the functional regulation of eEF1BdeltaL during heat shock.